1993
DOI: 10.1128/aem.59.8.2578-2588.1993
|View full text |Cite
|
Sign up to set email alerts
|

A Cytochemical Study of Extracellular Sheaths Associated with Rigidoporus lignosus during Wood Decay

Abstract: An ultrastructural and cytochemical investigation of the development of Rigidoporus lignosus, a white-rot fungus inoculated into wood blocks, was carried out to gain better insight into the structure and role of the extracellular sheaths produced by this fungus during wood degradation. Fungal sheaths had a dense or loose fibrillar appearance and were differentiated from the fungal cell wall early after wood inoculation. Close association between extracellular fibrils and wood cell walls was observed at both ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…However, we have, as yet, no evidence to support this. A similar phenomenon has been observed in wood-rotting fungi (Ruel & Joseleau, 1991 ;Nicole et al, 1993 ;Nicole, Ruel & Ouellette, 1994) and cassava bacterial blight caused by Xanthomonas campestris pv. manihotis (Boher et al, 1995).…”
Section: supporting
confidence: 75%
“…However, we have, as yet, no evidence to support this. A similar phenomenon has been observed in wood-rotting fungi (Ruel & Joseleau, 1991 ;Nicole et al, 1993 ;Nicole, Ruel & Ouellette, 1994) and cassava bacterial blight caused by Xanthomonas campestris pv. manihotis (Boher et al, 1995).…”
Section: supporting
confidence: 75%
“…Plants of resistant, but not susceptible, cultivars to A. rabiei were able to resist fungal penetration. ES contains polysaccharides and glycoproteins which are produced by various fungi (Nicole et al, 1993). TEM and cytochemical techniques have provided direct information on the roles ES may play in host-interactions.…”
Section: Discussionmentioning
confidence: 99%
“…This material may represent the melanin responsible for wood discolouration. Sheaths have been reported for other fungi (Gallagher & Evans, 1990;Daniel et al, 1992) and have been shown to contain wood-degrading enzymes (Ruel & Joseleau, 1991;Green HI et al, 1992;Nicole et al, 1993). As has been suggested for other fungi in wood, the sheaths might protect enzymes from inactivation and retain extracellular enzymes close to the micro-organism, offering a nutritional competitive advantage to the fungus in vivo (Wood, 1985;Kalisz, Wood & Moore, 1987;Green III et al, 1992).…”
Section: ' Gharibian and Othersmentioning
confidence: 90%